Valproic acid protects against MPP+-mediated neurotoxicity in SH-SY5Y Cells through autophagy. (18th January 2017) - Zhang, Y.; Wu, J.Y.; Weng, L.H.; Li, X.X.; Yu, L.J.; Xu, Y.
Highlights: VPA counteract MPP + -induced autophagic flux impairment in SH-SY5Y Cells. Autophagy induced by VPA play a role in neuroprotection. Autophagy induced by VPA alleviates apoptosis, reduces ROS production and MMP loss caused by MPP + . Abstract: Autophagy is a common physiological activity in cells. Studies show that dysregulation of autophagy is involved in the pathogenesis of Parkinson's disease (PD). As a commonly used anti-epileptic drug, valproic acid (VPA) has shown neuroprotective effects in PD. The aim of this study was to explore whether the autophagy induced by VPA involved in the neuroprotective effects in PD cell model. We found that VPA treatment counteracted MPP + -caused autophagic flux impairment. Forthermore, VPA could alleviates apoptosis, reduce reactive oxygen species (ROS) production and mitochondrial membrane potential (MMP) loss caused by MPP + . And we also observed that VPA up-regulated the active caspase-3 and Bcl-2/Bax ratio and inhibited cytochrome c (Cyt c) release from mitochondria to the cytoplasm. However, 3-Methyladenine (3-MA) or bafilomycin A1 (Baf-A1), blockers for autophagy, partially weakened the neuroprotective effect of VPA. Our findings suggest that the neuroprotective effect of VPA on neuroblastoma cells may partially result from inducing autophagy and related to the inhibition of the mitochondrial apoptosis pathway.